Who Will Lead Next? A Qualitative Study on Leadership Succession Planning in a Malaysian Dental School - Galvin Sim Siang Lin; Wai Wah Wong; Dara Khorsyiah Yakob; Carey Ai Chen Lim; Lara T. Friedlander (Education in Medicine Journal, 2026)
Within higher education, leadership succession planning fosters institutional stability and sustainability. This qualitative study explored the perceived challenges and strategies related to leadership succession planning among faculty leaders at a Malaysian public dental school. Semi-structured interviews were conducted with eight senior faculty members. Thematic analysis identified four major themes: (a) challenges in leadership succession planning; (b) strategies for succession planning; (c) impacts of succession planning; and (d) qualities of future leaders. Challenges highlighted included five sub-themes: unclear role descriptions, insufficient training for leadership positions, staff shortages and workload constraints, faculty reluctance towards leadership roles, and leadership turnover and organisational instability. Strategies included faculty documentation and guidelines, and talent identification and mentoring. The impacts of succession planning were faculty continuity and leadership sustainability, and faculty development and organisational culture. Meanwhile, future leaders required credibility and leading by example, adaptability, and selflessness and effective communication skills. These findings suggested the need for well-structured leadership succession planning to promote long-term growth and resilience. It also provided valuable insights to help other schools adopt the present framework and enhance their succession planning processes.